1999
DOI: 10.1038/sj.ejcn.1600875
|View full text |Cite
|
Sign up to set email alerts
|

Dual-energy X-ray absorptiometry for body composition estimation in Chinese women

Abstract: Objective: To determine whether dual-energy X-ray absorptiometry (DXA) is a valid method for body composition assessment of obese and non-obese subjects. Design: Cross-sectional study. Subjects: Chinese women living in Hong Kong; 66 of 91 subjects had body mass index (BMI) of b 25 kgam 2 . Measurements: Anthropometrics, including body weight, body height, waist and hip girth. Percentage body fat (%BF) and fat-free mass (FFM) from DXA (Hologic 2000 plus, Enhanced Array Whole Body Version 5.63) were compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 23 publications
0
10
1
1
Order By: Relevance
“…These rates are similar to results in a study from France and the UK but are lower than in studies from the USA (15%) [18]. The percentage of overweight subjects in this study was lower than in a previous study of Chinese women from Hong Kong [31]. Although BMI can be used as a marker for obesity, WHR is a better indicator of metabolic disorders.…”
Section: Discussioncontrasting
confidence: 29%
“…These rates are similar to results in a study from France and the UK but are lower than in studies from the USA (15%) [18]. The percentage of overweight subjects in this study was lower than in a previous study of Chinese women from Hong Kong [31]. Although BMI can be used as a marker for obesity, WHR is a better indicator of metabolic disorders.…”
Section: Discussioncontrasting
confidence: 29%
“…We measured body composition in a large population with a relatively accurate method, DEXA, which has been validated in Chinese populations (He et al 1999), thus reducing measurement errors from using surrogate measures such as anthropometry or bioelectrical impedance.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have suggested that the BF% derived by DXA may be underestimated compared to the 4C method in Asians. 24,25 For comparison with African Americans, Japanese, Caucasians, and other ethnic groups, the 4C-BF was estimated using Gallagher's equation, 5 and not measured directly by the standard method according to Heymsfield et al 16 However, Asians have higher BF% than Caucasians for any given BMI. As Gallagher's equation was mainly developed from Caucasians, it is reasonable to observe a relatively lower BF% measured by 4C than by DXA in Taiwanese.…”
Section: Menmentioning
confidence: 99%